The Lepidostoma coreanum Species Complex (Trichoptera, Lepidostomatidae) in the Asian Far East - Ito, Tomiko (Zootaxa, 2016)
A total of 68 species of genus Lepidostoma Rambur (Trichoptera; Lepidostomatidae) has been reported from the Asian Far East. L. coreanum (Kumanski & Weaver 1992) was originally described from North Korea. Detail examination of specimens of this species and its related specimens collected in the Asian Far East revealed the hypothetical definition of L. coreanum and the presence of 4 new related species, L. niigataense sp. nov., L. hattorii sp. nov., L. yuwanense sp. nov., and L. ishigakiense sp. nov. The species assemblage is named as the Lepidostoma coreanum Species Complex.